Successful treatment of nivolumab and ipilimumab triggered type 1 diabetes by using sodium-glucose transporter 2 inhibitor: a case report and systematic review - Fujiwara, Makoto; Shimizu, Masaru; Okano, Tatsuya; Maejima, Yuko; Shimomura, Kenju (Frontiers in Public Health, 2023)
Objective Checkpoint inhibitors (CPIs) can trigger complications related to the autoimmune process such as CPI-triggered diabetes mellitus. The typical treatment for CPI-triggered diabetes is insulin, but a detailed therapeutic method has not yet been established. To prevent severe symptoms and mortality of diabetic ketoacidosis in advanced-stage cancer patients, the establishment of effective treatment of CPI-triggered diabetes, other than insulin therapy, is required. Methods We present a case of a 76-year-old man with CPI-triggered diabetes who was treated with nivolumab and ipilimumab for lung cancer. We also conducted a systematic review of 48 case reports of type 1 diabetes associated with nivolumab and ipilimumab therapy before June 2023. Results The patient’s hyperglycemia was not sufficiently controlled by insulin therapy, and after the remission of ketoacidosis, the addition of a sodium-glucose transporter (SGLT) 2 inhibitor, dapagliflozin, improved glycemic control. Most of the reported nivolumab/ipilimumab-induced type 1 diabetes was treatable with insulin, but very few cases required additional oral anti-diabetic agents to obtain good glucose control. Conclusion Although SGLT2 inhibitors have been reported to have adverse effects on ketoacidosis, recent studies indicate that the occurrence of ketoacidosis is relatively rare. Considering the pathological mechanism of CPI-triggered diabetes, SGLT2 inhibitors could be an effective choice if they are administered while carefully monitoring the patient’s ketoacidosis.